Detection and identification of fungal species by electronic nose technology: A systematic review - Mota, Inês (2021)
A rapid and effective identification of fungal species is essential for numerous applications, and electronic nose systems are being proposed as suitable alternatives to currently available fungi identification techniques. Hence, the present review aims to unveil all published information concerning fungi identification by electronic nose systems. A systematic review of the literature was conducted according to the PRISMA guidelines. A total of 16 articles met the inclusion criteria and were included in the analysis. The results of the reviewed studies demonstrated that effective detection of fungi was possible through sensor-based electronic nose systems, which may actually function as a mycotoxin screening tool for several applications. The obtained results suggest that the sensor-based electronic nose systems may not only screen different fungi genera, but also identify the associated species. This technology has already been experimented in several fields, from food industry to clinical practice. By summarizing these results, the present review may accelerate the standardization of electronic noses in fungi detection and discrimination, allowing a faster and more efficient screening of samples.